SOME MODERN DRAMATIC FORMS IN THE ALBANIAN THEATRE - Puka, Gezim (European Scientific Journal, ESJ, 2013)
﻿Drama is the most canonic and conservative literary form, connected with the theatre as a medium and is influenced by the institutional cultural level of a country. It was this theatre that disbursed with great desire the Albanian drama setting it at the top of its repertoire and thus bringing some specific phenomena of ethno-psychological and customary nature. Drama processing, under the guidance of socialist realism, was formalized in Albania. The theatre became the place of dissemination of the ideology of the time. During the 90’s the dramatic genre changes its course from realist drama towards a modern and postmodern one. The dramas of Serafin Fanko, Stefan Capaliku and Albri Brahusha came to know the success in different contests, but the impact on the reader spectators was reduced. These works functioned as an ironic metacommunication with the other texts. The ironic dialogue of these works with the Bible or the ancient legends of the Albanians brought on stage works of postmodern nature. The article, through a method of surveying artistic texts, metatexts, periodicals and archives, intends to analyze why the best efforts to save the dramatic genre from the crisis are done exactly by these modern texts of these authors. Although their reception has not been major, aesthetic sensitivity is better stimulated through this kind of theatre, the critical spirit, the reasoning and judgment of the reader spectator is refined to make it perceive intense communicative and stimulating experiences either from cultural or human perspective.